Jumping performance is preserved but not muscle thickness in collegiate volleyball players after a taper - Bazyler, C. D.; Mizuguchi, S.; Sole, C. J.; Suchomel, T. J.; Sato, K.; Kavanaugh, A. A.; DeWeese, B. H.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to examine changes in muscle architecture and jumping performance in NCAA division I women's volleyball players throughout a competitive season and in preparation for conference championships. Ten women volleyball players were tested at preseason (T1), pretaper (T2), and post-taper (T3) on measures of vastus lateralis muscle thickness (MT), pennation angle (PA) and fascicle length (FL) using ultrasonography, and unloaded and loaded squat jump height (SJH) and peak power allometrically scaled to body mass (SJPPa) on a force platform. Rating of perceived exertion training load and strength training volume load were monitored weekly. Player's MT (p < 0.001, Glass's d = 2.8) and PA increased (p = 0.02, d = 3.9) after in-season training. However, MT decreased after the taper (p = 0.01, d = 0.6) but remained elevated above preseason values (p < 0.001, d = 1.7). There were no statistical changes in FL, SJH, or SJPPa. Large-to-very large negative relationships (r = -0.51 to -0.81) were observed between preseason relative maximal strength and changes in SJH and SJPPa with various loads over the season. These findings demonstrate that relatively low volumes of strength training and concurrent sport training during a tapering period are capable of preserving jumping performance, but not MT in women's volleyball players; however, jumping performance changes seem to be related to the player's strength level. Stronger players may benefit from an overreaching microcycle before the taper to preserve previously accrued muscular adaptations and jumping performance.